Integration of Virtual Labs into Science E-learning - Sun, Y. (2015)
Students can obtain lab content information equally well from two types of laboratories: a virtual and a physical lab. There is great potential in applying a 3D virtual lab based games to support teaching and learning in science. Moreover, it is significant to find practical ways to design and develop intelligent systems based on 3D games with limited complexity forms. 3D virtual environments provide an immersion into the learning contents, and interactions within the virtual world of the game, which are governed by established scientific principles. Therefore, people are looking for the forms of computer simulation - training that require fewer organizational and logistic efforts. Among them, three-dimension virtual environment is the important part of this system in enhancing the learning process. This paper aims to design and implement 3D virtual labs, which are considered as a low-cost alternative to educators and students, in science E-learning. This study focuses on the virtual assembly of instruments, the realization of dynamic 3D gauges, and the setup of emulation-based systems, which are key factors to provide students with the high-immersion 3D virtual lab. It also describes the setup of the network environment of this virtual lab; in this network, the server controls the options, user operations and the processes of experiments. Finally, this research involves designing and deploying a complex application that combines advanced visualization, interactive management through complex virtual devices and intelligent components.